Evaluation of the susceptibility to green stem disorder in soybeans [Glycine max (L.) Merr.] with vegetative storage protein accumulation - Jiuning Zhang; Tatsuhiko Shiraiwa; Tomoyuki Katsube-Tanaka (Plant Production Science, 2023)
ABSTRACTGreen stem disorder (GSD) is an important agronomical problem in soybean production because it delays leaf and stem senescence and complicates the harvest. However, a rapid and precise diagnosis of GSD has not yet been established. In this study, the effect of depodding on GSD and vegetative storage protein (VSP) accumulation was investigated in GSD-susceptible cultivar ‘Tachinagaha (Tc)’ and GSD-resistant experimental line ‘Touhoku 129 (Th)’ under two different (early and late) sowing dates in 2020 and 2021. Intact Tc plants showed relatively severe GSD at early sowing in 2020 and late sowing in 2021, whereas intact Th plants showed little GSD at both sowing dates and in both years. Meanwhile, depodding reproducibly induced GSD and increased stem weight for both Tc and Th. The relative VSP content peaked 14–21 days after R3 (DAR3) in intact plants and increased afterward in depodded plants. The relative VSP content differed at 28 DAR3 between intact and depodded plants, which was earlier than the timing when SPAD (soil plant analysis development) values differed, suggesting that VSP accumulation might be a better indicator of GSD than the SPAD value. The present study will contribute to the development of tools for diagnosing GSD.